Talent identification and development of youth athletes in football - Wilson, J. G. (Journal of Australian Strength and Conditioning, 2017)
Talent identification has become common practice among football clubs to find the best and most promising young players. However, the effectiveness of this process is arguable especially when identifying players before puberty. Bridging the gap between identification and reaching senior elite level requires a multifactorial approach of development in a number of areas. This article aimed to review the use of talent identification in football, the current problems with talent identification and current development models. Suggestions have also been made on how development can be improved in academies. Searches for the following keywords - youth, football (or soccer), elite, development, talent identification - were done through both PubMed and SPORTDiscuss between 2000 and 2017 and from this 44 articles were reviewed. Football academies spend a large amount of money on talent identification, yet sacrifice development for winning. There are a number of development models which suggest many factors should be the focus as opposed to just focusing on skills and fitness. Talent identification should still be utilised but as a means of informing training where development staff recognise a player`s weaknesses and work towards improving them. Academies will also benefit from a multidisciplinary team providing a holistic approach to development. This includes development through skills, tactical, physiological, psychological and social components (i.e. developing mental toughness).